The Level of Instagram's Influence on Millennials' Education Towards the Golden Generation - Besta Gulo; Muhammad Dhafa; M Arif Ridwan; Supina Batubara (Yayasan Sinergi Multidimensi Kreatif, 2024)
In this digital era, Instagram has become one of the most popular social media platforms among millennials. This article investigates the influence of Instagram as a tool to improve education and learning among millennials, with a focus on efforts towards creating a